2005
DOI: 10.1291/hypres.28.797
|View full text |Cite
|
Sign up to set email alerts
|

Association between Carotid Hemodynamics and Asymptomatic White and Gray Matter Lesions in Patients with Essential Hypertension

Abstract: The aim of this study was to clarify the magnitude of common carotid artery (CCA) structural and hemodynamic parameters on brain white and gray matter lesions in patients with essential hypertension (EHT). The study subjects were 49 EHT patients without a history of previous myocardial infarction, atrial fibrillation, diabetes mellitus, impaired glucose tolerance, chronic renal failure, symptomatic cerebrovascular events, or asymptomatic carotid artery stenosis. All patients underwent brain MRI and ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 40 publications
3
25
2
1
Order By: Relevance
“…Hypertensive patients with left ventricular hypertrophy had a higher stiffness β and lower CSDC and Vd/Vs than normotensive subjects (17). We have also reported a negative correlation between Vd/Vs and the severity of asymptomatic cerebral deep gray matter lesions, "etat crible," estimated by brain MRI (29). In the present study, we found a significant correlation between CAVI and stiffness β, CSDC, and Vd/Vs, in addition to IMT, suggesting that CAVI may serve as a useful clinical marker of arteriosclerosis and atherosclerosis.…”
Section: Discussionsupporting
confidence: 54%
“…Hypertensive patients with left ventricular hypertrophy had a higher stiffness β and lower CSDC and Vd/Vs than normotensive subjects (17). We have also reported a negative correlation between Vd/Vs and the severity of asymptomatic cerebral deep gray matter lesions, "etat crible," estimated by brain MRI (29). In the present study, we found a significant correlation between CAVI and stiffness β, CSDC, and Vd/Vs, in addition to IMT, suggesting that CAVI may serve as a useful clinical marker of arteriosclerosis and atherosclerosis.…”
Section: Discussionsupporting
confidence: 54%
“…The most frequently tested variable has been IMT, which was found increased in association to brain MRI lesions [9] [18] [26]. Nevertheless, this association was not encountered very recently by Heliopoulos et al in a sample of 52 hypertensive patients (mean age 71.4 years), nor in the present study.…”
Section: Discussioncontrasting
confidence: 53%
“…Changes in macrocirculation can be assessed by high-resolution B-mode ultrasonography. Limited studies have evaluated the relation between WMHs on brain MRI and ultrasound assessments of structural macrocirculation-vessel changes with partly conflicting findings [9]- [12]. Due to the high cost and low availability of MRI studies, the use of carotid Doppler as a potential marker of asymptomatic cerebral damage remains a very attractive option.…”
Section: Introductionmentioning
confidence: 99%
“…Plaque was defined as the presence of wall thickening of 50% or greater than the thickness of the surrounding wall, with a minimum absolute thickness of 1.1 mm. [17][18][19] Observation of plaque was performed from 4.5 cm proximal to 1.5 cm distal to the bifurcation. Twodimensional guided M-mode tracings of the bilateral CCA at a point 2 cm proximal to the bulb from the anterior, lateral and posterior approaches were recorded with an electrocardiogram, 18 and the internal diameters of the CCA at end-diastole (Dd) and peak-systole (Ds) were measured in three cycles and averaged.…”
Section: Evaluation Of Carotid Atherosclerosismentioning
confidence: 99%
“…[17][18][19] Observation of plaque was performed from 4.5 cm proximal to 1.5 cm distal to the bifurcation. Twodimensional guided M-mode tracings of the bilateral CCA at a point 2 cm proximal to the bulb from the anterior, lateral and posterior approaches were recorded with an electrocardiogram, 18 and the internal diameters of the CCA at end-diastole (Dd) and peak-systole (Ds) were measured in three cycles and averaged. 19 Axial resolution of the ultrasonography system was 0.1 mm.…”
Section: Evaluation Of Carotid Atherosclerosismentioning
confidence: 99%